(untitled) (Socio-Economic Development Panorama, 2008)
Rapid economic and technological development is imperative towards ushering into an accelerated development led society. No country can remain isolated from each other. All countries are directly or indirectly dependent upon each other. Highly developed countries rely heavily on the markets of the developing countries. Likewise, developing countries need to import development materials and manufactured products from developed as well as other developing countries. They need to export their primary and manufactured goods on the production of which they have a comparative advantage. Therefore, in this age of modern world, external sector performance has been growing at a rapid space. The external sector activities of Nepal are also growing significantly. Its trade relation is associated with more than one hundred countries. Nepal started to institutionalize its international trade against the backdrop of the beginning of development plans initiated in 1956. Since then, it has been adopting trade promotion policies for ensuring sustainable development of the external sector. This paper discusses briefly the international trade policies of Nepal and the challenges that it encounters. Keywords: international trade policies, import development strategy, sustainable development, trade policies, structural adjustment program, world trade organization, promotion of markets, backward and forward linkages, investment Socio Economic Development Panorama, Vol. 1, No.3(2008) pp. 65-78